PENAMBAHAN BAKTERI ASAM LAKTAT TERENKAPSULASI UNTUK MENEKAN PERTUMBUHAN BAKTERI PATOGEN PADA PROSES PRODUKSI TAPIOKA - Glisina Dwinoor Rembulan; Titi Candra Sunarti; Anja Meryandini (Jurnal Teknologi dan Industri Pangan, 2015)
Lactic acid bacteria (LAB) produce organic acids and active compounds which can inhibit the growth of pathogenic bacteria. Lactic acid bacteria potentially can be introduced to inhibit pathogenic bacteria in the tapioca production at the extraction stage, especially during the settling process since there is possibility of starch slurry to be contaminated by pathogenic bacteria from water. The objectives of this research were to design a solid starter of LAB through encapsulation by using modified starch includes sour cassava starch, lintnerized cassava starch and nanocrystalline starch, utilize the starter for suppressing the growth of pathogenic bacteria in the production process of tapioca and characterize the functional properties of tapioca. The encapsulation of lactic acid bacteria was conducted by freeze drying at a temperature of -50°C for 48 hours. The viability of LAB after freeze drying with sour cassava starch matrix was 92% of the liquid starter, with lintnerized cassava starch matrix was 93%, while that with nanocrystalline matrix was 96%. After application of the LAB culture during settling process for tapioca extraction and the tapioca was stored at room temperature for 6 months, it was shown that E. coli, Salmonella and Shigella were  detected in the native tapioca starch (without treatment) while the starch added with lactic acid bacteria starter was not absent for the pathogenic bacteria. The addition of lactic acid bacteria in extraction process can suppress the growth of pathogenic bacteria in tapioca. The results showed that lintnerized cassava starch matrix is the best matrix because after 6 months it still contained lactic acid bacteria as compared to liquid starter and that encapsulated with other matrixes.